Alternating Influence of Northern Versus Southern‐Sourced Water Masses on the Equatorial Pacific Subthermocline During the Past 240 ka. (18th November 2017) - Rippert, Nadine; Max, Lars; Mackensen, Andreas; Cacho, Isabel; Povea, Patricia; Tiedemann, Ralf
Abstract: The eastern equatorial Pacific (EEP) is a key area to understand past oceanic processes that control atmospheric CO2 concentrations. Many studies argue for higher nutrient concentrations by enhanced nutrient transfer via Southern Ocean Intermediate Water (SOIW) to the low‐latitude Pacific during glacials. Recent studies, however, argue against SOIW as the primary nutrient source, at least during early Marine Isotope Stage 2 (MIS 2), as proxy data indicate that nutrients are better utilized in the Southern Ocean under glacial conditions. New results from the subarctic Pacific suggest that enhanced convection of nutrient‐rich Glacial North Pacific Intermediate Water (GNPIW) contributes to changes in nutrient concentrations in equatorial subthermocline water masses during MIS 2. However, the interplay between SOIW versus GNPIW and its influence on the nutrient distribution in the EEP spanning more than one glacial cycle are still not understood. We present a carbon isotope (δ 13 C) record of subthermocline waters derived from deep‐dwelling planktonic foraminifera Globorotaloides hexagonus in the EEP, which is compared with published δ 13 C records around the Pacific. Results indicate enhanced influence of GNPIW during MIS 6 and MIS 2 compared to today with largest contributions of northern‐sourced intermediate waters during glacial maxima. These observations suggest a mechanistic link between relative contributions of northern and southern intermediate waters and past EEP nutrient concentrations. A switch from increased GNPIW (decreased SOIW) to diminished GNPIW (enhanced SOIW) influence on equatorial subthermocline waters is recognized during glacial terminations and marks changes to modern‐like conditions in nutrient concentrations and biological productivity in the EEP. Key Points: Reoccurring nutrient leakage from northern‐sourced waters to equatorial Pacific subthermocline waters during peak glacials Diminished Southern Ocean Intermediate Water nutrient influence on equatorial Pacific subthermocline during peak glacials High‐latitude water source switches to the equatorial Pacific during terminations